0.345 Attenuation Law of Vibration Signals During Caving - Xu Li; Tao Gu (Institute of Advanced Engineering and Science, 2014)
To study on the characteristics of the vibration signals of coal and stone hitting the armor plate during caving, a hybrid algorithm based on first order forward difference and wavelet transform modulus-maxima method is presented which can be used in the longwall top coal face. First, in order to reduce the noise interference, the pre-processing of the vibration signals is done by the first order forward difference method. Second, the wavelet transform modulus-maxima method is used to analyze the resluts of the difference for the post-processing of the data. Finally, attenuation formula is defined in the first-level details (D1). We can learn by the experimental results that the hybrid algorithm provides real-time, high confidence identification of coal and stone by analysis of the first-level details that has approximate 0.345 attenuation law between the wavelet transform modulus-maxima (the maximum coefficient) and the wavelet transform modulus-minima (the minimum coefficient). Because the wavelet transform modulus-maxima’s abscissa and the wavelet transform modulus-minima’s abscissa are adjacent to each other, the concept of Singularity-point Couple(SPC) is defined. Based upon the attenuation law and the defined concept, interference signals can be eliminated, vibration signals can be restored, and some prediction work can be done. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4885